Polyethylene-based blends, composites and nanocomposites - P. M., Visakh; Martínez Morlanes, María Jose (Wiley, 2015)
"The book focusses on the recent technical research accomplishments in the area of polyethylene-based blends, composites and nanocomposites by looking at the various aspects of processing, morphology, properties and applications. In particular, the book details the important developments in areas such as the structure-properties relationship of polyethylene; modification of polyethylene with radiation and ion implantation processes; stabilization of irradiated polyethylene by the introduction of antioxidants; reinforcement of polyethylene through carbon-based materials as additives; characterization of carbon-based polyethylenes composites, polyethylene-based blends with thermoplastic and thermoset; characterization of polyethylene-based thermoplastic and thermoset blends; polyethylene-based blends with natural rubber and synthetic rubber; characterization of polyethylene-based natural rubber and synthetic rubber blends; characterization of polyethylene-based composites"--